2022
DOI: 10.1039/d2tc01010k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing hole carrier injection via low electrochemical doping on circularly polarized polymer light-emitting diodes

Abstract: Circularly polarized electroluminescence (CP-EL) from a blend system of chiral small-molecule additives and device optimised achiral π-conjugated polymers (π-CPs) is of great interest for next-generation display technologies. However, CP polymer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…They have a g EL of À0.65 and 0.3, respectively. 81,82 These results indicate that F8BT with chiral helical structure has great application potential in CP-OLED. [78][79][80]82 In 2020, Zou et al found that after the irradiation of left-handed or right-handed CPL light, the CPL signal can be measured from achiral luminescent polymer F6BT.…”
Section: Cpl Based On Chiral Induced Helical Polymersmentioning
confidence: 80%
See 2 more Smart Citations
“…They have a g EL of À0.65 and 0.3, respectively. 81,82 These results indicate that F8BT with chiral helical structure has great application potential in CP-OLED. [78][79][80]82 In 2020, Zou et al found that after the irradiation of left-handed or right-handed CPL light, the CPL signal can be measured from achiral luminescent polymer F6BT.…”
Section: Cpl Based On Chiral Induced Helical Polymersmentioning
confidence: 80%
“…81,82 These results indicate that F8BT with chiral helical structure has great application potential in CP-OLED. [78][79][80]82 In 2020, Zou et al found that after the irradiation of left-handed or right-handed CPL light, the CPL signal can be measured from achiral luminescent polymer F6BT. 83 The intensity and direction of the generating CPL signal are strongly influenced by the polarization direction and irradiation wavelength of the chiral source CPL light.…”
Section: Cpl Based On Chiral Induced Helical Polymersmentioning
confidence: 80%
See 1 more Smart Citation
“…At first, holes or electrons are generated in the valence band and the conduction band of the conjugated polymer by redox doping, photoexcitation, or charge injection, respectively. [28][29][30] Subsequently, the holes or electrons would distort the nearby lattice structures to lower their energy levels, forming localized topological excitons, e.g., soliton, polaron, bipolaron, as the charge carriers. Based on the reduction of energy by lattice distortion, the energy levels of the charge carriers from high to low can be written as soliton 4 polaron 4 1 2 bipolaron.…”
Section: John H Xinmentioning
confidence: 99%
“…In particular, various CPL materials have been developed for electroluminescent applications in circularly polarized organic light-emitting diodes (CP-OLEDs). [19][20][21][22][23][24][25][26] How to realize a high luminescence dissymmetry factor (g lum ), which characterizes the level of polarization and is defined by g lum = 2(I L À I R )/(I L + I R ) (where I L and I R are the emission intensity of left-handed and right-handed circularly polarized light, respectively), has been the key challenge in the field to promote the practical applications of CPL materials.…”
mentioning
confidence: 99%